GAMBARAN KECERDASAN EMOSIONAL DAN PRESTASI BELAJAR PADA SISWA NEGERI XI MANADO - Alfiah, Gesti; Opod, H.; Sinolungan, J.` S.V. (Universitas Sam Ratulangi, 2013)
Abstract: Emotional intelligenceis the ability to recognize one's own emotions, managing emotions themselves, motivating one self, recognizing emotions in others, managing emotions in others and motivate others. While learning achievementis the resultof a study of learning activities based on the measurement and assessment of learning outcome sin academic areas are embodied in the form of number sin there port card. When students have high emotional intelligence, it will improve learning achievement. Susceptible adolescents aged 11-16 years with astudent status, emotional intelligence is the ability to regulate one's emotional life with intelligence. The research objective was to determine the level of the general purpose of emotional intelligenceand learning achievementin students, a special purpose to know the descriptionof emotional intelligence that is about recognizing your own emotions, managing emotions yourself, motivate yourself and recognize other people's emotions, managing emotions in others, as well as motivating others, and learning achievement at the student has with an average value of report cards. The study population was Manado XI Junior High School student sin 2011/2012. Data collection procedures using a questionnaire. The data presented in tabular form as well as analysis of the frequency distribution of cross presentation use. Conclusion: The study found that emotional intelligence is and average student achievements were. Key Words: emotional intelligence, learning on student achievement Abstrak: Kecerdasan emosional adalah kemampuan seseorang untuk mengenali emosi diri sendiri, mengelola emosi diri sendiri, memotivasi diri sendiri, mengenali emosi orang lain, mengelola emosi orang lain dan memotivasi orang lain. Sedangkan prestasi belajar adalah hasil belajar dari suatu aktivitas belajar yang dilakukan berdasarkan pengukuran dan penilaian terhadap hasil kegiatan belajar dalam bidang akademik yang diwujudkan berupa angka-angka dalam rapor. Bila siswa memiliki kecerdasan emosional yang tinggi, maka akan meningkatkan prestasi belajar. Remaja dengan rentang usia 11-16 tahun yang berstatus siswa, kecerdasan emosional adalah kemampuan seseorang mengatur kehidupan emosinya dengan intelegensi. Tujuan penelitian adalah tujuan umum untuk mengetahui tingkat kecerdasan emosional dan prestasi belajar pada siswa, tujuan khusus untuk mengetahui gambaran kecerdasan emosional yakni tentang mengenali emosi diri sendiri, mengelola emosi diri sendiri, memotivasi diri sendiri dan mengenali emosi orang lain, mengelola emosi orang lain, serta memotivasi orang lain, dan prestasi belajar pada siswa yakni tentang nilai rata rata raport. Populasi penelitian adalah siswa SMP Negeri XI Manado tahun 2011/2012. Prosedur pengambilan data dengan menggunakan kuesioner. Data disajikan dalam bentuk tabel serta analisis presentasi.dan menggunakan distribusi frekuensi silang. Simpulan: Hasil penelitian didapatkan bahwa kecerdasan emosional siswa sedang dan rata rata prestasi sedang. Kata kunci: kecerdasan emosional dan prestasi belajar pada siswa.